Central nervous system involvement in Multiple Myeloma—Diagnosis, treatment and outcome: A case report - Muhammad Uzair Ali; Shafaq Maqsood; Mahrukh Malik; Kausar Bano (Journal of the Pakistan Medical Association, 2021)
Multiple Myeloma is a clonal proliferation of plasma cells with bone marrow as the primary site of occurrence. Extramedullary multiple myeloma is uncommonly seen either at presentation or later during the course of the disease. Central nervous system involvement by multiple myeloma is an extremely rare entity with a dismal outcome. This case report focuses on 45yr old male who presented with bone aches. Investigation findings leading to diagnosis involved elevated calcium levels, lytic lesions on radiological examination and clonal plasma cells in bone marrow biopsy. During his treatment patient was given chemotherapy regimens containing Lenalidomide, Bortezomib, Cyclophosamide and Prednisolone. He developed neurological complications (CNS myelomatosis) thereafter, which resulted in his demise. The clinical presentation, diagnosis, treatment and outcome of this rare condition is detailed in these pages. Keywords: Multiple Myeloma, Extramedullary Multiple Myeloma, CNS Myelomatosis Continuous...